If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-707=-7(y-796)
We move all terms to the left:
-707-(-7(y-796))=0
We calculate terms in parentheses: -(-7(y-796)), so:We get rid of parentheses
-7(y-796)
We multiply parentheses
-7y+5572
Back to the equation:
-(-7y+5572)
7y-5572-707=0
We add all the numbers together, and all the variables
7y-6279=0
We move all terms containing y to the left, all other terms to the right
7y=6279
y=6279/7
y=897
| 2+5t+7t=50 | | 7f-19=4f | | 4x-3(-2x+1)=27 | | n/3+1=2 | | -354=5p+8(4p+2) | | 3/7(x-8)=1/4(2x+4) | | 127=5a-4(-10+2) | | B+1.5b+b+2b+45+90-90=540 | | -6(-q+8)=-16+12 | | 4x+5(3x+1)=-71 | | 5(x-6)=5-(4x-1) | | y/2.5+1.7=2.9 | | 5-5x=2(1-2x) | | 4=22×6y | | -25=-4m+3-21 | | 4(x+9)=x-15 | | -4x+6=7/5x+4/ | | (24a-22)+40=30a-12 | | h/71-6.5=1.2 | | 25x-4=121 | | 8x-3+5x-11+90=180 | | -4x+6=7/5X+4/7 | | 5m+7=9-3m | | 3(+n)-15=24 | | -4x+6=7/5+4/7 | | -9.3z-z(2+1/3)+(-2/3)=z | | 6a-8=a-6 | | 57=3(n-67) | | 6a-8=4a-6 | | x+25=2x-14 | | 136=4(7)(4)+2(4)(x) | | 7x+19=2x-6 |